RETRACTED: LOXL2 Upregulation in Gliomas Drives Tumorigenicity by Activating Autophagy to Promote TMZ Resistance and Trigger EMT - Zhang, Qing; Yang, Lianhe; Guan, Gefei; Cheng, Peng; Cheng, Wen; Wu, Anhua (Frontiers in Oncology, 2020)
Glioma is the most common primary brain tumor in adults and has an extremely poor prognosis. As a member of the lysyl oxidase (LOX) family, lysyl-oxidase-like-2 (LOXL2) is known to play different roles in different tumors. However, the biological function of LOXL2 in glioma remains unclear. In the present study, we showed that LOXL2 was markedly upregulated in glioma and that LOXL2 upregulation significantly correlated with glioma WHO grade, malignant molecular subtypes, and poor prognosis in glioma patients. Additionally, we found that LOXL2 not only promoted glioma cells proliferation, migration, and invasion and induced the epithelial-to-mesenchymal transition (EMT) process, but also reduced the sensitivity of glioma cells to TMZ. Furthermore, we identified that LOXL2 reduced TMZ sensitivity and induced EMT in glioma via the activation of autophagy. Mechanistically, LOXL2 enhanced Atg7 expression by promoting the phosphorylation of Erk1/2, leading to the activation of autophagy and regulation of EMT and TMZ sensitivity through autophagy. Our study describes an LOXL2-Erk1/2-Atg7 signaling axis that influences glioma EMT and chemosensitivity through autophagy; moreover, LOXL2 may serve as a promising therapeutic target in the treatment of glioma.